To Serve Man: A Marketing Manifesto (and an Article That Should Not Have Been Necessary) - Gaski, John F. (Journal of Public Policy & Marketing, 2013)
This conceptual offering embodies what may be a long-overdue but plainspoken metaphysical assessment of the basic nature of marketing. A point of emphasis is that chronic misdefinition and misinterpretation of marketing itself have impeded proper appreciation of marketing's positive impact on society. One purpose here is to correct that lingering miscomprehension (pervading even the highest reaches of scholarship) and appropriately position the business function of marketing taxonomically within the larger domain of economic and governance philosophy and the societal perspective. Armed with that insight, it becomes possible to dismiss as invalid much specious criticism of marketing. Improved understanding of the true nature of marketing in turn illuminates its macroeconomic and societal role. Therefore, the field of marketing may deserve to be celebrated more than it has been to date—not that it has been universally. This item's message is thus submitted, in constructive and therapeutic spirit, as perhaps the transcendent good news story that the marketing field has received.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTUwOS9qcHBtLjEyLjA5NQ